2016
DOI: 10.1017/s003060531600034x
|View full text |Cite
|
Sign up to set email alerts
|

Asian snake farms: conservation curse or sustainable enterprise?

Abstract: Snake farming in Asia has increased over the past decade, and conservationists have expressed concerns that farms may foster overexploitation of wild populations and create legal conduits for illegally harvested wild individuals. We conducted face-to-face interviews with snake farmers in Viet Nam and China, with the aim of describing the basic models under which snakes are farmed for meat. We synthesized this information to assess the feasibility of farming snakes for human consumption, drawing conclusions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Notably, all C. baileyi and C. parvum positive individuals were captive-bred and raised. Previous studies and our survey confirmed E. carinata , N. atra , N. kaouthia and P. mucosa are the most extensively farmed snake species since they accept dead or defrosted feeder animals, and thus are easy to be intensively farmed (Aust et al, 2017). All five captive snake species in our study were maintained on a diet of farm supplied quick-frozen defeathered young chicks of ducks, quails, and layer fowls along with their eggs.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Notably, all C. baileyi and C. parvum positive individuals were captive-bred and raised. Previous studies and our survey confirmed E. carinata , N. atra , N. kaouthia and P. mucosa are the most extensively farmed snake species since they accept dead or defrosted feeder animals, and thus are easy to be intensively farmed (Aust et al, 2017). All five captive snake species in our study were maintained on a diet of farm supplied quick-frozen defeathered young chicks of ducks, quails, and layer fowls along with their eggs.…”
Section: Discussionsupporting
confidence: 74%
“…There is a long history of exploitation of snakes in Asia in traditional medicine and as food. Snake farming is now extensive in China since the dietary habit has spread all over the country and was boosted by rapid economic growth (Aust et al, 2017). On three farms alone in Guangdong Province there were 40,000 captive-bred oriental rat snakes in a single year and captive bred snakes were occasionally released to reinforce the wild population (Jiang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although imposing a ban may appear to benefit python conservation, it is important to understand the potential impact of that management option on pythons in these countries, and the people relying on them (Weber et al 2015). Asian snakes have been traded for a variety of purposes for centuries (Natusch and Lyons, 2014;Aust et al 2016). Banning the international trade in skins is unlikely to discourage people from harvesting snakes, which will continue to be used for the domestic leather industry, traditional medicines and food.…”
Section: Should Trade Bans Be Considered?mentioning
confidence: 99%
“…While much of the scientific debate over wildlife farms has occurred in the conservation literature, other elements are also relevant to the discussion. Wildlife farms can provide livelihoods and/or food security to impoverished communities [ 24 , 25 ]. The economic impacts on communities depends upon the species and the geographic context.…”
Section: Introductionmentioning
confidence: 99%